2013
DOI: 10.1007/s00264-013-2043-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patellofemoral joint in ADVANCE® Medial-pivot total knee arthroplasty

Abstract: Purpose ADVANCE® Medial Pivot (MP) (Wright Medical) total knee arthroplasty (TKA) was established to replicate normal tibio-femoral knee joint kinematics, however, its influence on the patello-femoral (PF) joint is unclear. The purpose in this study was to assess the PF joint conditions in Advance MP TKA, via radiography and three-dimensional image-matching software. Methods Ten subjects with osteoarthritis were treated with the ADVANCE MP TKA. Pre-operatively and one month after surgery, skyline views at 30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
0
24
0
2
Order By: Relevance
“…Recently, medial pivoting knee motion has also been adopted in several knee replacement designs that are aimed to reproduce anatomic knee joint motion patterns (Chinzei et al, 2014; Ishida et al, 2012; Morra et al, 2008; Pritchett, 2011; Schmidt et al, 2003; Schmidt et al, 2014). However, our data showed that both the medial and lateral cartilage contacts are a convex femur to a convex tibia contact in sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, medial pivoting knee motion has also been adopted in several knee replacement designs that are aimed to reproduce anatomic knee joint motion patterns (Chinzei et al, 2014; Ishida et al, 2012; Morra et al, 2008; Pritchett, 2011; Schmidt et al, 2003; Schmidt et al, 2014). However, our data showed that both the medial and lateral cartilage contacts are a convex femur to a convex tibia contact in sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…The femoral rotational axis could be defined by the navigation system as the average rotation axis of the transepicondylar axis, and the axis perpendicular to the Whiteside line; we also determined the axis using preoperative three-dimensional planning software (Athena Knee), in which the axis was parallel to the surgical epicondylar axis [22,23]. The tibial rotational axis was defined along the line from the medial border of the tibial tubercle to the middle of the posterior cruciate ligament [24].…”
Section: Kinematic Measurements Of the Kneementioning
confidence: 99%
“…[15]; b MIS-Methode: Verhältnis der Länge der artikulierenden Patellarückfläche zur Länge des Lig. patellae [13]; c Blackburne-Peel-Methode: Verhältnis der Länge der artikulierenden Patellarück-fläche zum Lot zwischen dem kaudalstem Punkt der artikulierenden Patellarückfläche und der Tangente zur Tibiaplateauebene [9]; d Caton-Deschamp-Methode: Verhältnis der Länge der artikulierenden Patellarückfläche zum Abstand zwischen dem kaudalstem Punkt der artikulierenden Patellarückfläche und dem ventralstem Punkt des Tibiaplateaus [10] "patella" "unicompartmental replacement" "unicompartmental arthroplasty" "unicompartmental/ Abb. 1 9 Übersicht der Literaturrecherche zur Identifikation von relevanten Studien te eine negative Korrelation zum post operativen "Knee Society Score" aufwie sen. Niedrige präoperative ISWerte kor relierten negativ mit dem postoperativen "Knee Society Score".…”
Section: Patellahöheunclassified
“…In einer ähnlichen Studie evaluier ten Chinzei et al [10] die Veränderun gen von Patellaverkippung und laterali sation bei jeweils 30°, 60° und 90° Flexion. Hinsichtlich der Patellaverkippung zeigte sich postoperativ eine signifikante Zunah me nur bei 60° Flexion, während sich die Patellalateralisation bei allen gemessenen Beugestellungen signifikant verbesserte.…”
Section: » Mit Zunehmendemunclassified